Advances in Anti-tumor Therapy of Myeloid-derived Suppressor Cells Combined with Immunological Checkpoint Inhibitors - SUN Haiyan; GONG Lei; YU Zhentao; PAN Zhanyu (Zhongliu Fangzhi Yanjiu, 2020)
Immunity checkpoint inhibitors (ICI) can enhance the original anti-tumor immune response by restoring the identification and killing of T cells to tumor cells. ICI have been approved for melanoma, NSCLC and renal cells carcinoma, etc. However, many patients do not respond to immunotherapy due to immunosuppression, which is mediated partly by myeloid-derived suppressor cells (MDSCs). This heterogeneous population of immature bone marrow cells strongly inhibit the anti-tumor activity of T cells and NK cells and stimulate regulatory T cells (Treg), leading to tumor progression. MDSCs can promote the patient's resistance to immune checkpoint inhibition. Increasing evidence show that the proportion of MDSCs in cancer patients and immunosuppressive function can be used as the predictors of therapeutic response. This review highlights the role of MDSCs in the suppression of immune checkpoints and analyzes the combined strategy of MDSCs and ICI, to improve the therapeutic efficacy of cancer patients.